The role of male competition and female choice in the mating success of a Lek-breeding Southern African Cichlid fish Pseudocrenilabrus Philander (Pisces: Cichlidae) - Chan, Tin-Yam (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1988)
A lek-breeding cichlid fish Pseudocrenilabrus philander was studied experimentally. Females in choice-chamber experiments showed no active choice for male size and colour, or for other male attributes, but preferred males which courted most actively. In a laboratory lek, the significant determinants of the strongly skewed mating success in males were territory size, side-shake and female chasing frequency. Together these three variables explained 79% of the variation in male mating success, with territory size alone accounting for 75% of the variation and the other two variables each accounting for 2% of the remaining variation. As there was no difference in territory quality in the laboratory lek, territory size became the principal measure of the effect of male-male competition since it was directly related to dominance. Both side-shake and female chasing could be identified as the basic factors influencing female choice, as they had an immediate effect on the display-response mating system of females. Thus, the relative importance of these three variables indicated that sexual selection in this particular lek mating species operated chiefly through the agency of intrasexual competition for dominance. However, both female behaviour and their requirement for a prolonged pre-spawning courtship had the effect of promoting male rivalry and favouring mating with dominant males. Although the intense male competition excluded subordinate males from practising normal courtship behaviour, competitively inferior males might "make the best of a bad situation" by facultatively adopting an alternative sneaking tactic to gain access to females. Spawning intrusions by females to steal freshly-laid eggs also occurred frequently. However, territorial males appeared to be relatively more tolerant of female intruders than male sneakers. Interference during spawning could lead to a longer pre-spawning courtship and even multiple-mating by females. The results of the present study and the behavioural evidence shown by males and females did not support the Êºrunaway selection modelÊº of the mating pattern in terms of sexual selection in leks, but conformed to the rival Êºwar propaganda modelÊº
Keywords: Cichlids -- Africa, Southern -- Physiology; Courtship in animals; Fishes -- Reproduction; Cichlids; Pseudocrenilabrus philander; Lek behavior; Courtship; Reproduction; Spawning; Competition; Rivalry